Theology and Epistemology of Islamic Law - Dadang Syaripudin (International Journal of Nusantara Islam, 2021)
This article discusses the Theology and Epistemology of Islamic Law. This study uses a qualitative method with a literature review approach. The type of data is in the form of classical Islamic law narratives. The material sources are publications of classical Islamic law books. The data collection technique is in the form of tracking narratives in the works of classical Islamic law. The data analysis technique is in-depth descriptive. This article finds that law is a manifestation of Allah's will in the realm of Islamic Legal Theology and Epistemology. In Usul Fiqh, Allah is al-Hakim, al-Syari (lawmaker). Therefore, every attempt to formulate law is an attempt to discover the Will of Allah. However, His Will is not static, but rather the fundamental principles revealed and elaborated progressively. There is an epistemological debate in actualizing God's Will into a prescriptive legal formulation between ushul scholars from various kalam and schools of fiqh. Problems that always arise are related to approaches, methods, and sources to obtain valid knowledge to know God's law. In this case, at least three theological schools are dominant in influencing and shaping Islamic legal thought, especially in conceptualizing and categorizing legal actions into the rights of Allah and the rights of servants. The three schools are Mu'tazilah, Ash'ariyah and Maturidiyah.